Spor Liselerinde Öğrenim Gören Öğrencilerin Beden Eğitimi Dersine Karşı Tutumlarının Sportmenlik Davranışlarına Olan Etkisinin Incelenmesi - Çakır, Eren Bora (My University, 2025)
This study was conducted in order to examine how the interest of students studying in sports high schools in physical education and sports lessons, the way they perceive the lesson and their attitudes towards the lesson shape and affect their sportsmanship behavior. The research was conducted with 210 participants studying at official sports high schools affiliated with the Ministry of National Education in Istanbul between 01/10/2024 and Dec 25/11/2024. SPSS (Statistical Package for Social Sciences-IBM, Chicago, IL, USA) program was used in the statistical analysis of the data obtained in the research. According to the results of the study, it was found that gender did not make a significant difference on the students' sportsmanship behaviors. Differences in sportsmanship attitudes were found according to the class level; especially 9. and 12. Attitudes of grade students, 10. and 11. it has been observed that it remains at a lower level compared to classroom students. It has been observed that the maternal education level has a significant effect on the students' sportsmanship behaviors, and it has been determined that the children of mothers with undergraduate and graduate education levels exhibit positive attitudes. On the other hand, no significant difference was found in terms of the father's educational level or sports playing status. It has been found that students whose mothers do sports have higher sportsmanship and physical education lesson attitudes compared to the children of mothers who do not do sports. In the regression analysis results, it was found that cognitive activity has a significant and positive effect on sportsmanship behaviors, while affective and behavioral elements of activity are not significant. It has been determined that general attitudes related to physical education lessons contribute to the development of sportsmanship awareness and behavior. These findings show that the elements that will increase cognitive awareness should be emphasized in the content of physical education courses in sports high schools and that family participation is an important factor in the process of creating sportsmanship awareness.

Yapılan bu çalışma spor liselerinde öğrenim gören öğrencilerin beden eğitimi ve spor derslerine olan ilgilerinin, dersi algılama biçimlerinin ve derse karşı tutumlarının sportmenlik davranışlarını nasıl şekillendirdiğini ve etkilediğini incelemek amacıyla gerçekleştirilmiştir. Araştırma 01/10/2024 ile 25/11/2024 tarihleri arasında İstanbul'da yer alan Milli Eğitim Bakanlığına bağlı resmi spor liselerinde okuyan 210 katılımcı ile yapılmıştır. Araştırmada elde edilen verilerin istatistiksel analizinde SPSS (Statistical Package for Social Sciences-IBM, Chicago, IL, USA) programı kullanılmıştır. Çalışma sonuçlarına göre cinsiyetin öğrencilerin sportmenlik davranışları üzerinde anlamlı bir farklılık yaratmadığı görülmüştür. Sınıf düzeyine göre sportmenlik tutumlarında farklılıklar tespit edilmiş; özellikle 9. ve 12. Sınıf öğrencilerinin tutumları, 10. ve 11. sınıf öğrencilerine göre daha düşük seviyede kaldığı görülmüştür. Anne eğitim düzeyinin ise öğrencilerin sportmenlik davranışları üzerinde anlamlı bir etkiye sahip olduğu gözlemlenmiş, lisans ve lisansüstü eğitim düzeyine sahip annelerinin çocuklarının olumlu tutumlar sergilediği belirlenmiştir. Buna karşılık baba eğitim düzeyi veya spor yapma durumu açısından anlamlı bir fark bulunamamıştır. Annesi spor yapan öğrencilerin spor yapmayan annelerin çocuklarına kıyasla daha yüksek sportmenlik ve beden eğitimi dersi tutumlarına sahip olduğu saptanmıştır. Regresyon analizi sonuçlarında bilişsel etmenin sportmenlik davranışları üzerinde anlamlı ve pozitif bir etkisi olduğu; duyuşsal ve davranışsal unsurların ise etkinsin anlamlı olmadığı bulunmuştur. Beden eğitimi dersine ilişkin genel tutumların sportmenlik bilinci ve davranışlarının gelişimine katkı sağladığı belirlenmiştir. Bu bulgular spor liselerinde beden eğitimi derslerinin İçeriğinde bilişsel farkındalığı artıracak unsurların vurgulanması gerektiğini ve aile katılımının sportmenlik bilinci oluşturma sürecindeki önemli bir faktör olduğunu göstermektedir.
An Investigation of the Effect of Attitudes of Students Studying in Sports High Schools towards Physical Education Lessons on Sportsmanship
Keywords: Physical Education and Sports Lesson; High Schools of Fine Arts and Sports; Sports; Spor; Beden Eğitimi ve Spor Dersi; Güzel Sanatlar ve Spor Liseleri